Tor Andrae's Historical-Psychological Reading of theRevelation of Prophet Muhammad: A Study of Mohammed:The Man and His Faith - Muhammad Habib Izzuddin Amin (Al-Hikmah: International Journal of Islamic Studies, 2025)
This study explores the views of the Swedish orientalist Tor Andrae on the concept of revelation experienced by the Prophet Muhammad, as articulated in his work Mohammed: The Man and His Faith. Revelation serves as one of the theological foundations of Islam; however, in Western academic scholarship, it has often been approached through a variety of perspectives. This research seeks to fill a scholarly gap, as Andrae’s perspective on revelation has received relatively little attention compared to that of other scholars. Using a qualitative library research method and a content analysis approach, this study examines Andrae’s arguments and ideas concerning the revelation of the Prophet Muhammad. The findings indicate that Andrae perceives the Prophet’s revelation as an authentic and unexpected mystical experience, arising from the Prophet’s inner anxiety about the Day of Judgment. Nevertheless, Andrae rejects the notion that revelation emerged from a vacuum. He argues that the experience represents a synthesis of pre-existing theological ideas within the Arabian milieu. Thus, Andrae situates the Prophet Muhammad’s revelation not as a purely divine message, but as a complex psychological and historical phenomenon in which the Prophet absorbed and reformulated the non-Orthodox ideas that surrounded him.